TOPIC DECONGESTANTS IN COMPLEX THERAPY OF UPPER AIRWAYS DISEASES - G.D. Tarasova (Union of pediatricians of Russia, 2006)
In the complex treatment of the inflammatory diseases of ENT-organs (rhinitis, sinusitis, tubootitis and otitis media) vasoconstrictors (topic decongestants) are locally applied. Besides, they're used in diagnosing of nasal cavity diseases. Topic decongestants are produced as nasal drops and nasal sprays. Peculiarities of application of pharmaceuticals in children are dependent on inherent properties, particularly the duration of effect. These drugs each have proper dosage conditions that should be followed carefully in pediatric practice. Moreover, the physician must choose the efficient way of vasoconstrictor introduction into nasal cavity.Key words: edema, topic decongestants, ENT-organs diseases, rebound syndrome, children.